Solve for X

Asked by fathima12 | 10th Jun, 2010, 01:02: PM

Expert Answer:

Let, ax - by = a2 +b2 be eqn (1)
and x + y = 2a be eqn (2)
Multiplying the 2nd equation by a, we get
ax + ay = 2a2 ...............(3)
Now subtraction (3) from equation (1), we get
-(b+a)y = b2-a2
Therefore, y =
                  = a - b
Now, substituting the value of y in equation (2)
x + a - b = 2a
Therefore, x = a + b
 
Hence the required solution is x = a +b and y = a - b
 
Thanks,
Topper Learning Team

Answered by  | 14th Jul, 2010, 12:33: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.